PERAN PENYULUHAN PEMBANGUNAN DALAM MEMBENTUK PERILAKU DAN POLA HIDUP BERMUKIM RAMAH LINGKUNGAN - Wildani Pingkan S Hamzens (TATALOKA, 2012)
This study aims to see the important role of Development Extension on Urban Settlement and Housing Development Policy Implementation, particularly in efforts to establish Green Behaviour and Green Sattled Living Pattern. This research was conducted by Survey Method, with measures: (1) Develop Research Framework, (2) Select Research Location, (3) Conduct Observation and Interviews, (4) Process and Analyze Data, (5) Make Conclusion and Recommendation. Research shown that Development Extension related with effort to establish Green Behaviour and Green Settled Living Pattern had not conducted by the Developers nor Government, either prior to or after inhabitants occupied their houses in the settlement. The results conclude that in order to create Green Behaviour and Green Settled Living Pattern, an effective Development Extension activities are required. Development Extension can bridge the gap between development of the housing and urban settlement with development of the environmentally friendly human behaviour, hence it shall establish a Green Behaviour of Living and Environmentally Friendly Settled Living Pattern.